2021
DOI: 10.1037/per0000392
|View full text |Cite
|
Sign up to set email alerts
|

Triarchic or septarchic?—Uncovering the Triarchic Psychopathy Measure’s (TriPM) structure.

Abstract: The Triarchic Psychopathy Measure (TriPM) is based on a 3-dimensional conceptual model, though few studies have directly tested a 3-factor structure. The current study used a large community sample (N ϭ 1,064, 53% males, M age ϭ 34) to test the structure of the TriPM via exploratory and confirmatory factor analysis, along with 4 community replication samples from North American and Europe (Ns ϭ 511-603, 33-49% males) and 1 European male offender sample (N ϭ 150). Three of these samples were also used to model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 72 publications
1
54
2
Order By: Relevance
“…Patrick et al relied on a single sample of college students with TriPM data and presented results inconsistent with our analyses of general population samples, and some of their own previously published TriPM results (Somma et al 2019). Based on meta-analytic and structural research of the TriPM (Collison et al, 2020;Roy et al, 2020;Sleep et al, 2019;Stanton et al, 2020), there is clear evidence of multidimensionality for each triarchic scale and continued concerns regarding the structural validity of the TriPM. Moreover, the original TriPM scales used in contemporary research do not match up with the ESEM model that Patrick et al employ with item cross-loadings (some very large) and 153 correlated residuals.…”
Section: Limited Utility Of Broad Factors In Advancing Theory Developcontrasting
confidence: 64%
See 3 more Smart Citations
“…Patrick et al relied on a single sample of college students with TriPM data and presented results inconsistent with our analyses of general population samples, and some of their own previously published TriPM results (Somma et al 2019). Based on meta-analytic and structural research of the TriPM (Collison et al, 2020;Roy et al, 2020;Sleep et al, 2019;Stanton et al, 2020), there is clear evidence of multidimensionality for each triarchic scale and continued concerns regarding the structural validity of the TriPM. Moreover, the original TriPM scales used in contemporary research do not match up with the ESEM model that Patrick et al employ with item cross-loadings (some very large) and 153 correlated residuals.…”
Section: Limited Utility Of Broad Factors In Advancing Theory Developcontrasting
confidence: 64%
“…It is noteworthy that three recent studies involving TriPM item level analyses (9 samples in total) have all raised numerous concerns (Collison et al, 2020;Stanton et al, 2020;Roy et al, 2020) and the problems identified tend to be quite consistent irrespective of the approach used. All three studies identified similar problems such as poor statistical fit for the a priori triarchic model, items with poor psychometric properties (e.g., item cross-loadings, low factor loadings), and the presence of significant multidimensionality within the TriPM domains.…”
Section: Inherent Multidimensionality Within Triarchic Model Frameworkmentioning
confidence: 83%
See 2 more Smart Citations
“…One of the alternative frameworks of psychopathy that addresses the above multiple psychopathy types principle, is the Triarchic Psychopathy Model. Patrick et al (2009) have proposed this conceptualization based on the observation that previous literature reveals three important facets within the construct of psychopathy: boldness (reduced emotionality, resilience to stress, and social dominance), meanness (lack of empathy, cruelty, and aggressive behavior toward others), and disinhibition (impulsivity and dysregulation of negative affect) (but see Roy et al, 2020 for a septarchic structure of this model). These three constructs are viewed as connected, yet distinct from one another, and can be measured and understood separately.…”
Section: Subtypes Of Psychopathymentioning
confidence: 99%